The Ideal Cardinal and the Role of the Papacy in Dell’uffizio del cardinale (1599) by Giovanni Botero (Theatrum historiae, 2019)
The paper aims to highlight the principal topics of Giovanni Botero’s speech Dell’uffizio del cardinale (1599), the first part of it being dedicated to show what cardinals could do to improve Catholicism in the Reformation world, and the second one, known as Discorso intorno allo Stato della Chiesa, is based on the analysis of the papacy as an independent state: a state that was regional but with universal pretensions.
Keywords: Giovanni Botero; cardinal; Eastern Europe; papacy; politics; Reason of state